Influence of amyloid beta on impulse spiking of isolated hippocampal neurons - Yavorsky, Volodymyr A.; Rozumna, Nataliia M.; Lukyanetz, Elena A. (Frontiers in Cellular Neuroscience, 2023)
One of the signs of Alzheimer’s disease (AD) is the formation of β-amyloid plaques, which ultimately lead to the dysfunction of neurons with subsequent neurodegeneration. Although extensive researches have been conducted on the effects of different amyloid conformations such as oligomers and fibrils on neuronal function in isolated cells and circuits, the exact contribution of extracellular beta-amyloid on neurons remains incompletely comprehended. In our experiments, we studied the effect of β-amyloid peptide (Aβ1–42) on the action potential (APs) generation in isolated CA1 hippocampal neurons in perforated patch clamp conditions. Our findings demonstrate that Aβ1–42 affects the generation of APs differently in various hippocampal neurons, albeit with a shared effect of enhancing the firing response of the neurons within a minute of the start of Aβ1–42 application. In the first response type, there was a shift of 20–65% toward smaller values in the firing threshold of action potentials in response to inward current. Conversely, the firing threshold of action potentials was not affected in the second type of response to the application of Aβ1–42. In these neurons, Aβ1-42 caused a moderate increase in the frequency of spiking, up to 15%, with a relatively uniform increase in the frequency of action potentials generation regardless of the level of input current. Obtained data prove the absence of direct short-term negative effect of the Aβ1–42 on APs generation in neurons. Even with increasing the APs generation frequency and lowering the neurons’ activation threshold, neurons were functional. Obtained data can suggest that only the long-acting presence of the Aβ1–42 in the cell environment can cause neuronal dysfunction due to a prolonged increase of APs firing and predisposition to this process.